EFISIENSI DAN DIFERENSIASI MERUPAKAN SYARAT UTAMA MEMENANGKAN PERSAINGAN BISNIS DI ERA PERKEMBANGAN TEKNOLOGI KEUANGAN YANG SANGAT PESAT PADA PERUSAHAAN MANUFAKTUR SEKTOR ANEKA INDUSTRI - R. Gatot Heru Pranjoto (Eco-Entrepreneur, 2018)
To win the competition in globalization, companies must be able to achieve production efficiency, as well as win the hearts of customers by providing innovative and consistent products. Production efficiency can be proven by the growth of earnings greater than output growth or can be said the company to obtain maximum operating leverage. The position of product offerings on the market is very important, how the company can lead the market, for that company must be able to understand the needs of customers by offering innovative products with competitive prices, it is expected that the company can generate sales turnover that has maximum earning power